Book Review: Vasiliev, A.M. (2018). From Lenin to Putin. Russia in the Middle East. Moscow: Tsentrpoligraf publ., 670 p. (in Russian) - Liudmila Vasilievna Ponomarenko; Galina Olegovna Lukianova (Vestnik RUDN. International Relations, 2018)
-